TINGKAT PENDIDIKAN IBU MEMILIKI HUBUNGAN DENGAN STATUS PERKEMBANGAN MOTORIK HALUS ANAK USIA PRASEKOLAH - Agus Warseno (Jurnal Keperawatan Malang, 2019)
Development in preschool children can be seen from fine motor development. One of the factors that can influence development in children is the education factor of parents, especially mothers. The purpose of this study was to determine the relationship between maternal education and fine motor development in preschool children. This research method is quantitative non-experimental, with a cross sectional approach. The study was conducted at Margomulyo Sleman Sleman Kindergarten and the determination of respondents using a total sampling technique of 41 people. Data collection using questionnaires and DDST II. Data analysis uses the Spearman correlation test with a significance level of p <0.05. The results of the study showed that most of the last education taken by mothers was high school, which was 23 people (56.1%). Most preschoolers in Margomulyo Sleman Kindergarten showed normal fine motor development, namely 33 people (80.5%) and children who showed suspect fine motor development as many as 8 people (19.5%). The results of the Spearman correlation test obtained p-value 0.023 (? = 0.05). Correlation coefficient of 0.354. There is a relationship between maternal education and fine motor development in preschool children.